O avanço da internacionalização abrangente sob diferentes pontos de análise: um estudo com instituições de ensino superior do Rio Grande do Sul - Gazzoni, Fernando (2021)
The process of internationalization of higher education is no longer a question or possibility, it is a certainty and necessity in a globalized world, being possible to be involved in this process in different ways and levels. Several countries and institutions have been investing in the development of policies for the internationalization of higher education. This endeavor is beginning to be considered of strategic importance as investment in education is the main means of generating knowledge. In Brazil, the internationalization of higher education is no longer an incipient situation, but it still less advanced compared to other countries. For internationalization to advance in Brazilian higher education, it is necessary to insert internationalization strategies into the strategic planning of institutions and propel institutional culture towards internationalization. This would lead to comprehensive internationalization which aims to integrate the different institutional internationalization strategies covering the entire institution, seeking to change the institutional ethos and learning outcomes. Against this background, this study seeks to provide an overview of the current status of comprehensive internationalization of six federal universities in the state of Rio Grande do Sul. Through a multi-method approach, different sources that directly interfere in the development of the institutions' internationalization policies were analyzed. The sources examined are the institutional strategic plans related to the internationalization process, the perception of institutional actors, and the legislation used to support the internationalization plans. Among the sources analyzed there is a focus on policies and actions related to the movement of people and the achievement of cooperation agreements with a focus on mobility actions. There is a perceived prioritization of actions of the type abroad, while actions of the at home type are underdeveloped. The internationalization of Brazilian higher education is still characterized by the absence of public policies to guide the development of the institutions' internationalization process. Institutional actors do recognize the importance of internationalization; however, there is a feeling that it is still an activity developed by few people and is more intrinsic to postgraduate studies. Barriers to the development of a comprehensive internationalization process may include the absence of a policy for continuing education for teachers, the difficulty in establishing an assessment process, the offer of internationalized courses in the disciplines, and the absence of variables for measuring learning outcomes. Given this situation, the results of the study showed that, although with hesitance, internationalization has advanced in the researched institutions; however, there is still a long way to go before comprehensive internationalization is achieved. The development of this thesis sought to elucidate the current panorama of comprehensive internationalization in the national scenario. The scope of this analysis can be further expanded by future studies analyzing individual axes of comprehensive internationalization, the achievement of forms of assessment of comprehensive internationalization, and learning outcomes, among other topics.